Manejo de plantas daninhas sobre a temperatura do solo, eficiência no uso da água e crescimento da cultura do pimentão nos sistemas de plantio direto e convencional - Coelho, Maria Eliani Holanda (Universidade Federal Rural do Semi-Árido, 2011)
Three experiments were carried out in the didactic orchard of the Departamento de Ciências Vegetais of Universidade Federal Rural do Semi-Árido (UFERSA), located in Mossoró-RN. The experiments aimed at assessing the interference of weeds on the soil temperature, on the growth of sweet pepper (Capsicum annuum L.), and on the efficiency as to the use of water in the referred to type of crop when submitted to weed handling strategies within the systems no-trillage and conventional planting. The trials were assembled in a split-plot scheme, distributed within the experimental design , in randomized blocks with four replications. Within the plots, two planting systems were assessed (no-trillage and conventional), and, within the subplots, three weed handling strategies soil covering with black polyethylene film, with regular weeds, and with no weeds, were assessed. Within each subplot, sensors were installed at a depth of 5 cm for the purpose of measuring the soil temperature. Data were collected every 10 minutes and stored in dataloggers. As for the first experiment, the collected data led to the determination the temperature variation throughout the day from 20 to 30 days after transplanting (DAT), the average maximum and minimum temperatures every 5 days, and the daily temperature range during the crop cycle. On the 60th and 147th days after transplanting, the density as well as the dry mass of the weeds were assessed within the treatment with no weeds. Regarding the second experiment, what was assessed was the growth of sweet pepper, submitted to weed handling strategies within no-trillage and conventional planting systems. To attain such an objective, eight assessment times were established (0, 21, 42, 63, 84, 105, 126 e 147 DAT). The assessed features were: leaf area per plant, leaf area index, dry mass of leaves, of stem, of fruits, and the total dry mass per plant, leaf area ratio as well as the rates of absolute and relative growth and of net assimilation. On the 30th and 90th DAT, the weeds density and the dry mass were assessed in the treatments with no weeds. As to the third experiment, the water consumption and the sweet pepper s productivity were assessed. Based upon the relationship between productivity and water consumption, the efficiency as with water use (kg of fruit m-³ of water) was determined. On 0, 21, 42, 63, 84 e 105 DAT, the density and dry mass of weeds were assessed in the treatments with no weeds. Irrigation was done by way of dripping water, with different water supply to each subplot in order that the soil would be maintained with at least 80% of the total available water, based upon water tension in the soil. It was found that the soil temperature was influenced by the covering types, with wider temperature ranges and maximum temperatures in the treatments with weeds and in the treatments with the soil covered by polyethylene film within the conventional planting system as compared to the no trillage direct planting with regular weeds. The no-trillage system proved to be a suitable technique for growing sweet peppers under a high temperature condition. The no-trillage system displayed higher growth rates than those displayed by the conventional planting in all weed handling strategies. The highest rates were observed in the no-trillage with weeds; besides, this type of planting reduces infestation and the weeds dry mass accumulation. Insofar as the third trial is concerned, it was found that the weeds interference increased water consumption and reduced the sweet pepper productivity within the two planting systems; however, the conventional planting displayed stronger effects. The treatment with weeds in the direct planting displayed greater fruit productivity and greater efficiency as for water use as compared to the others. It was concluded that the dead covering in the direct planting lowered the soil temperature, favored the growth and productivity of sweet pepper, reduced infestation by weeds, and increased water use efficiency
Weed handling on soil temperature, efficiency as to the use of water, and growth of sweet peppers cultivated in no-trillage and conventional planting
Keywords: Capsicum annuum L.; Temperature range; Growth analysis; Save water; Dead covering; Plastic mulch; Capsicum annuum L.; Amplitude térmica; Análise de crescimento; Economia de água; Cobertura morta; Filme de polietileno; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA